Applications of Au25 Nanoclusters in Photon-Based Cancer Therapies - Zoey A. Lockwood; Michael R. Jirousek; James P. Basilion; Clemens Burda (Nanomaterials)
Atomically precise gold nanoclusters (AuNCs) exhibit unique physical and optical properties, making them highly promising for targeted cancer therapy. Their small size enhances cellular uptake, facilitates rapid distribution to tumor tissues, and minimizes accumulation in non-target organs compared to larger gold nanoparticles. AuNCs, particularly Au25, show significant potential in phototherapy, including photothermal (PTT), photodynamic (PDT), and radiation therapies. These therapies benefit with minimal damage to surrounding healthy tissue. AuNCs also demonstrate excellent stability and biocompatibility, crucial for their effective use in clinical applications. Recent advances in the synthesis and functionalization of AuNCs have further improved their therapeutic efficacy, making them versatile agents for enhancing cancer treatment outcomes. Ongoing research aims to better understand their pharmacokinetics, biodistribution, and long-term safety, paving the way for their broader application in advanced cancer therapies.